2005
DOI: 10.1248/cpb.53.984
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibitors from the Heartwood of Vietnamese Caesalpinia sappan

Abstract: From the MeOH extract of Vietnamese Caesalpinia sappan, a novel biogenetically exclusive benzindenopyran, with a new carbon framework, neoprotosappanin (1), and a new compound, protosappanin A dimethyl acetal (3), were isolated together with protosappanin E-2 (2), neosappanone A (4), and 13 previously reported phenolic compounds (5-17). Their structures were elucidated on the basis of spectroscopic data. Compounds 1-4, 7, 13, and 15-17 showed significant xanthine oxidase inhibitory activity in a concentration-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 17 publications
0
42
0
2
Order By: Relevance
“…Only a few studies were conducted of compounds other than 1, such as the anti-complementary activity 19) of 7 and the xanthine oxidase inhibitory activity 20) of 2. Our previous study revealed that 2 showed similar anti-oxidant activity to 1, 16) suggesting that the anti-inflammatory effect of CSE is due to not only 1.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies were conducted of compounds other than 1, such as the anti-complementary activity 19) of 7 and the xanthine oxidase inhibitory activity 20) of 2. Our previous study revealed that 2 showed similar anti-oxidant activity to 1, 16) suggesting that the anti-inflammatory effect of CSE is due to not only 1.…”
Section: Discussionmentioning
confidence: 99%
“…XO inhibitors may be useful for treatment of these diseases. For the treatment of hyperuricemia and gout allopurinol, oxypurinol, and febuxostat have been used widely (Higgins et al, 2011;Nguyen et al, 2005).…”
Section: Chythrantus Claneianusmentioning
confidence: 99%
“…Novel inhibitors of XO may be beneficial in various diseases [Perez-Ortiz et al, 2007]. The XO [Nguyen et al, 2005] and 2,2-diphenyl-l-picrylhydrazyl radical (DPPH) assays [Acuna et al, 2002;Braca et al, 2002] have been routinely used to evaluate antioxidant activity due to free radical generation and scavenging and were employed to compare the antioxidant activity E. senticosus and R. rosea…”
Section: Introductionmentioning
confidence: 99%